Potential anti-acne loaded nanogel formulations of Origanum majorana L. and Chrysanthemum morifolium Ramat. essential oils - Eman A. Kotb; Riham A. El-Shiekh; Mariam Hassan; Wessam Hamdy Abd-Elsalam; Nebal El Tanbouly; Amira Safwat El Senousy (Applied Biological Chemistry, 2024)
Abstract Acne is a highly prevalent skin disease with a great psychological impact on patients as self-perception, self-confidence, and depression. This work aimed to develop an anti-acne preparation from active anti-bacterial medicinal plants to circumvent the severe side effects and drug resistance commonly reported with topical erythromycin anti-acne preparations. Essential oils: Salvia officinalis L. (sage), Rosmarinus officinalis L. (rosemary), Commiphora myrrha Nees Engl. (myrrh), Origanum majorana L. (marjoram), Pelargonium zonale L. L’Hér. ex Aiton (geranium) and Chrysanthemum morifolium Ramat. (chrysanthemum) were extracted by hydrodistillation and analyzed using gas chromatography/mass spectrometry (GC/MS). The anti-acne activities of the oils against Cutibacterium acnes ATCC 6919 were evaluated by microdilution methods to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The most active essential oils were loaded in a film-forming nanogel prepared with chitosan, pluronic F127 and glycerol in the ratio of 3:1:1, prior to investigation in a murine acne in vivo model. Marjoram and chrysanthemum oils showed the highest antimicrobial activity against C. acnes (MIC = 0.156% v/v and 0.125% v/v, respectively). GC/MS of the actives showed that gamma-terpinene (26.46%) and terpinen-4-ol (22.24%) were the predominant constituents in marjoram, whereas chrysanthenone (32.79%) was the main component in chrysanthemum. The formulated essential oil-loaded film-forming nanogels of both oils exhibited significant anti-acne activity in mice via reducing the bacterial loads, activating the antioxidant nuclear factor erythroid 2–related factor 2 (Nrf2) pathway and inhibiting the inflammatory tumor necrosis factor-alpha (TNF-α) pathway. Further studies should be designed to evaluate the clinical evidence for the use of marjoram and chrysanthemum oil products in acne treatment. Graphical Abstract